ENHANCING STUDENTS’ MOTIVATION IN LEARNING ENGLISH WITH CLIL APPROACH - Sahril, Mohamad; Kamila, Qarira Muti Kamila (ELLITE ( Journal of Education, Linguistics, Literature and Language Teaching), 2024)
This study aims to determine the extent to which the Content and Language Integrated Learning (CLIL) approach can increase students' motivation in learning English. Using a qualitative approach with a case study design, data were collected through semi-structured interviews with six students of the English Education study program who attended CLIL-based lectures. Data were analyzed thematically based on the Self-Determination Theory (SDT) framework. The results showed that CLIL had a positive impact on students' intrinsic and extrinsic motivation. Students feel more interested, involved, and internally motivated because the material is delivered contextually and relevantly. In terms of extrinsic motivation, academic demands and professional goals encourage them to study harder. The conclusion of this study shows that the implementation of CLIL can be an effective strategy in increasing motivation to learn English. The implication of this finding is the importance of curriculum development and teacher training that supports the sustainable implementation of CLIL in higher education.